PHONEMIC INTERFERENCE: GENERAL CONCEPTS AND THEORETICAL BASIS (Web of Teachers: Inderscience Research, 2025)
This article examines the general concept and theoretical foundations of phonemic interference, analyzing its linguistic and psycholinguistic aspects. Phonemic interference is a linguistic phenomenon that occurs due to the influence of one phonemic system on another, particularly noticeable in bilingual and multilingual environments. The article discusses the causes, main types, and manifestations of interference. Additionally, it explores strategies for preventing and minimizing phonemic interference. This research has significant practical value in linguistics and language acquisition studies.